Logic, Language, Information and Computation 18th International Workshop, WoLLIC 2011, Philadelphia, PA, USA. Proceedings - Beklemishev, Lev D.; Queiroz, Ruy.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 18th Workshop on Logic, Language, Information and Communication, WoLLIC 2011, held in Philadelphia, PA, USA, in May 2011. The 21 revised full papers presented were carefully reviewed and selected from 35 submissions. Among the topics covered are various aspects of mathematical logic, computer science logics, philosophical logics, such as complexity theory, model theory, partial order, Hoare logics, hybrid logics, Turing machines, etc.
Keywords: Computer science; Computer software; Logic design; Computational complexity; Algebra -- Data processing; Computer Science; Mathematical Logic and Formal Languages; Logics and Meanings of Programs; Algorithm Analysis and Problem Complexity; Computation by Abstract Devices; Discrete Mathematics in Computer Science; Symbolic and Algebraic Manipulation